2005
DOI: 10.1107/s0907444905028805
|View full text |Cite
|
Sign up to set email alerts
|

Structure of human semicarbazide-sensitive amine oxidase/vascular adhesion protein-1

Abstract: Semicarbazide-sensitive amine oxidase (SSAO) belongs to a ubiquitous family of copper-containing amine oxidases (CuAOs). SSAO is also known as vascular adhesion protein-1 (VAP-1) and has been identified as one of the adhesion molecules involved in the leukocyte-extravasation process. The structure of a truncated soluble form of human SSAO has been solved and refined to 2.5 A. As expected, SSAO is a homodimer with a fold typical of the CuAO family. The topaquinone (TPQ) cofactor and a copper ion characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(105 citation statements)
references
References 71 publications
3
102
0
Order By: Relevance
“…We observed that the corresponding Lys 24 , Lys 28 , Lys 61 , Lys 62 , and Lys 65 residues, which generate a positively charged surface on the S. cerevisiae Atx1 protein, are either replaced by Arg (instead of Lys) for the first 2 residues or perfectly conserved for the last 3 residues in S. pombe Atx1. It is therefore possible that Atx1 docks on the cavity of the entry channel at the active site of Cao1, which is predicted to have the capacity to retain relatively large substrates, particularly those with multiple positively charged Lys residues with NH 2 groups on their surface (27). In fact, it is known that peptides with exposed lysines can associate with and inhibit human Cao1/Vap1-dependent lymphocyte rolling activity (53).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the corresponding Lys 24 , Lys 28 , Lys 61 , Lys 62 , and Lys 65 residues, which generate a positively charged surface on the S. cerevisiae Atx1 protein, are either replaced by Arg (instead of Lys) for the first 2 residues or perfectly conserved for the last 3 residues in S. pombe Atx1. It is therefore possible that Atx1 docks on the cavity of the entry channel at the active site of Cao1, which is predicted to have the capacity to retain relatively large substrates, particularly those with multiple positively charged Lys residues with NH 2 groups on their surface (27). In fact, it is known that peptides with exposed lysines can associate with and inhibit human Cao1/Vap1-dependent lymphocyte rolling activity (53).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Solving of the crystal structure of VAP-1 dimer revealed that it is a heart-shaped dimer consisting of 4 domains per monomer. 20,21 On the top of the molecule there are multiple O-and N-linked oligosaccharides, which may be important for its adhesive function. 22 There is also a groove on the surface of VAP-1 which opens into narrow and deep substrate channel leading to the catalytic center of the molecule buried relatively deep inside each monomer.…”
Section: Figurementioning
confidence: 99%
“…It has been proposed that H 2 O 2 may induce conformational changes in SSAO due to sulfydryl-group oxidation to form a vicinal disulfide bond, and that this may play an important role in modulating its actions [28]. However, the amount of H 2 O 2 generated during the oxidation of benzylamine under the conditions used in the present work would be very small.…”
Section: Discussionmentioning
confidence: 82%
“…The studies reported here show that some L-lysine derivatives also to interact with SSAO, although the simple substituted derivatives were considerably less potent as inhibitors. Steric factors may be important if interaction occurs at the active site, since substrates must penetrate a narrow entrance cavity in order to access the catalytic system [27,28]. Some small lysine-containing peptides have been reported to to inhibit SSAO [31,32].…”
Section: Discussionmentioning
confidence: 99%